Des améliorations locatives - H., J. (Assurances)

(untitled) (HEC Montréal, 1985)
What, exactly, do "Leasehold lmprovements" mean? And who should insure them to see that the insurance interest rule is applied? Here, the author strives to explain this often used, yet generally vague, expression.